Buffer Management and Packet Loss Avoidance Using Random Early Passive Proactive Prediction Queue Management And Cluster Based Multipath Reliable Congestion Control Protocol - Purushotham, B; Ch D V Subba Rao, Dr. (International Journal of Engineering and Technology, 2018)
Mobile adhoc network is one of the wireless sensor networks which consist of collection of nodes that helps to transmit the information from source to destination. During the information transmission, it has faced several problems such as packet loss because of the buffer overflow and frequent link failure due to the mobility of the nodes present in the Manet. For overcoming these issues, in this paper introduces the routing and buffer management technology for reducing the packet loss as well as effectively transmit the information from source to destination. Initially the buffer has been managed in the Manet with the help of the random early detection passive proactive prediction queue management technique (REDPPPQM) which effectively manages the length of the packets also utilize the resources with effective manner, more over it reduces the packet loss and reduces the limitation present in the PAQMN. After buffering the packets, optimized route has been predicted with the help of the cluster based multipath reliable congestion control protocol which grouping the similar packets into gather and the optimized route has been detected that avoids the packet loss as well as saving the energy while transmitting the information in the Manet. At last the efficiency of the system is evaluated with the help of the experimental results and discussions in terms of the packet loss ratio, transmission efficiency, throughput and mobility.Â Â